2014
DOI: 10.1007/s00277-014-2164-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lenalidomide in relapse/refractory multiple myeloma—Real life experience of a tertiary cancer center

Abstract: Lenalidomide was approved for the treatment of relapsed and refractory multiple myeloma (rrMM) based on MM009 and MM010 clinical trials. However, its effectiveness and safety profile in real clinical practice should be further assessed. We retrospectively evaluated 90 consecutive patients treated in our center with lenalidomide and dexamethasone (LenDex) between 2007 and 2012. The overall response rate to this treatment was 68 % and the median duration of response was 13.6 months. Patients treated in first rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 27 publications
6
14
4
Order By: Relevance
“…Nearly 50% of patients in our study had previously undergone ASCT, a rate that is consistent with the range of 49%-62% reported previously in the literature (4,5,8,14). In our study, the ORR was 73%, with a CR rate of 19%; these rates are comparable with those reported in the literature (61%-78% and 6%-21%, respectively) (6)(7)(8)12,13). In a Dutch compassionate-use study, in which patients had received a median of three previous lines of treatment, the ORR and CR + very good partial response (VGPR) rate were 69% and 25%, respectively (13).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nearly 50% of patients in our study had previously undergone ASCT, a rate that is consistent with the range of 49%-62% reported previously in the literature (4,5,8,14). In our study, the ORR was 73%, with a CR rate of 19%; these rates are comparable with those reported in the literature (61%-78% and 6%-21%, respectively) (6)(7)(8)12,13). In a Dutch compassionate-use study, in which patients had received a median of three previous lines of treatment, the ORR and CR + very good partial response (VGPR) rate were 69% and 25%, respectively (13).…”
Section: Discussionsupporting
confidence: 92%
“…This reflects the fact that, in Turkey, reimbursement is provided with bortezomib treatment following two cycles of conventional chemotherapy in patients with newly diagnosed MM under the age of 65. Another difference versus other studies was the lower usage of thalidomide: 13% in our study versus 23%-64% in previous reports (4,5,8). This again can be attributed to reimbursement considerations, in addition to concerns regarding the risk of thalidomide-induced neuropathy.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Notably, neutropenia and infection have also been associated with LEN therapy in previous studies of advanced MM. [28][29][30] In this study, grade 4 neutropenia and neutropenic complications were more common with isatuximab 10 mg/kg Q2W than in either of the QW/Q2W cohorts. Grade 3/4 thrombocytopenia occurred in approximately one-third of patients, a rate similar to that reported in previous studies of LEN therapy in advanced MM.…”
Section: Discussionmentioning
confidence: 82%
“…Overall, no important drug-related treatment-emergent AEs were observed in the current trial beyond those anticipated based on previous studies of LEN-Dex alone. [28][29][30] In this study, the combination of isatuximab-LEN-Dex demonstrated encouraging clinical activity, with an ORR of 56% and a CBR of 71% in the efficacy-evaluable population. At data cutoff, the median PFS was 8.5 months and the median duration of response across all groups was 10.9 months.…”
Section: Discussionmentioning
confidence: 93%